2015
DOI: 10.1007/s11064-015-1553-x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Glia Maturation Factor Protects Dopaminergic Neurons and Improves Motor Behavior in Mouse Model of Parkinsonism

Abstract: Previously, we have shown that aberrant expression of glia maturation factor (GMF), a proinflammatory protein, is associated with the neuropathological conditions underlying diseases suggesting an important role for GMF in neurodegeneration. In the present study, we demonstrate that absence of GMF suppresses dopaminergic (DA) neuron loss, glial activation, and expression of proinflammatory mediators in the substantia nigra pars compacta (SN) and striatum (STR) of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
2
20
0
1
Order By: Relevance
“…GMF-induced neuroinflammation leads to the death of neurons in the CNS (Zaheer et al, 2007). GMF expression level is increased in the CNS of neurodegenerative diseases including EAE (Zaheer et al, 2011b; Thangavel et al, 2012), while GMF knockdown suppresses dopaminergic neuronal loss, glial activation and the expression levels of proinflammatory mediators in the substantia nigra of MPTP-treated animal model of PD (Khan et al, 2015). We have previously reported the expression of GMF in human and mouse mast cells, as GMF was also reported in several extra CNS cells in the body (Kempuraj et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GMF-induced neuroinflammation leads to the death of neurons in the CNS (Zaheer et al, 2007). GMF expression level is increased in the CNS of neurodegenerative diseases including EAE (Zaheer et al, 2011b; Thangavel et al, 2012), while GMF knockdown suppresses dopaminergic neuronal loss, glial activation and the expression levels of proinflammatory mediators in the substantia nigra of MPTP-treated animal model of PD (Khan et al, 2015). We have previously reported the expression of GMF in human and mouse mast cells, as GMF was also reported in several extra CNS cells in the body (Kempuraj et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that GMF-deficiency in astrocytes upregulates antioxidant level and reduces the production of ROS in MPP + -induced toxicity [8]. Our another study showed that absence of GMF suppresses dopaminergic neuronal loss, glial activation, and expression of inflammatory mediators in the SNpc and striatum of MPTP treated mice [15]. We also recently demonstrated MPP + -induced dopaminergic neuronal loss in primary cultures of the mouse mesencephalic neurons/glia obtained from GMF-KO and wild-type mice [54].…”
Section: Discussionmentioning
confidence: 99%
“…Glia maturation factor (GMF), a brain protein previously isolated, sequenced and cloned in our laboratory [912] has reported to activate glial cells and induce neuroinflammation and neurodegeneration in vivo and in vitro [1315]. Overexpression of GMF increased Experimental Autoimmune Encephalomyelitis (EAE) disease severity and induced significant releasee of proinflammatory cytokines and chemokines from astrocytes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of GMF expression causes inflammation in neurodegenerative disorders [6]. It was for the first time discovered, purified, sequenced and sub-cloned from bovine brain in our laboratory [712]. Previous reports from our laboratory showed that GMF is mainly co-localized and expressed in the vicinity of Aβ and tau in the temporal cortex of human AD brain [13, 14].…”
Section: Introductionmentioning
confidence: 99%